2019 IEEE Conference on Multimedia Information Processing and Retrieval (MIPR) 2019
DOI: 10.1109/mipr.2019.00080
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Object Detection of Images from Network Cameras in Variable Ambient Lighting Conditions

Abstract: Computer vision relies on labeled datasets for training and evaluation in detecting and recognizing objects. The popular computer vision program, YOLO ("You Only Look Once"), has been shown to accurately detect objects in many major image datasets. However, the images found in those datasets, are independent of one another and cannot be used to test YOLO's consistency at detecting the same object as its environment (e.g. ambient lighting) changes. This paper describes a novel effort to evaluate YOLO's consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Two images of the same scene can be captured by the same camera less than a second apart, yet the predictions of a neural network on those two visually similar images can differ dramatically. The small differences between the two images are called image distortions, and they can be caused by a range of factors, including ambient light level and camera sensor noise [13].…”
Section: Synthetic Image Distortions and Data Augmentationmentioning
confidence: 99%
See 3 more Smart Citations
“…Two images of the same scene can be captured by the same camera less than a second apart, yet the predictions of a neural network on those two visually similar images can differ dramatically. The small differences between the two images are called image distortions, and they can be caused by a range of factors, including ambient light level and camera sensor noise [13].…”
Section: Synthetic Image Distortions and Data Augmentationmentioning
confidence: 99%
“…As Tung, et al [13] observe, popular image datasets (e.g., ImageNet, Microsoft COCO) are filled with visually dissimilar images. Thus, those datasets are largely unsuitable for consistency testing.…”
Section: Considerations When Measuring Consistencymentioning
confidence: 99%
See 2 more Smart Citations
“…However, these methods are specifically implemented for place recognition or robot localization problems, and cannot be applied to appropriate perception of objects of interest under short- and long-term context or environment changes. Tung et al (2019) evaluated YOLO’s (Redmon et al, 2016) performance during long-term changes on detecting an object of interest over long periods of time under various lighting conditions. It was observed that YOLO continuously struggles to detect the same object during sudden changes and during night time.…”
Section: Related Workmentioning
confidence: 99%